2011
DOI: 10.2174/1874285801105010144
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Severe Respiratory Syncytial Virus Lower Respiratory Tract Infection

Abstract: RSV infection is a leading cause of lower respiratory tract infection, especially in High-risk infants with a history of prematurity, bronchopulmonary dysplasia (BPD), congenital heart disease (CHD), neuromusculair impairment, immunodeficiency, and Down syndrome. Host related risk factors that have been identified to be associated with severe RSV related lower respiratory tract infection include young age below 6 months at the beginning of RSV season, multiple birth, male sex, low socioeconomic status and pare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

23
190
4
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 200 publications
(219 citation statements)
references
References 62 publications
(105 reference statements)
23
190
4
2
Order By: Relevance
“…Although recent studies, most of which were retrospective assessments, have consistently shown RSV hospitalizations to be the highest in the first year of life, very few have dissected the exact age of RSV-specific hospitalizations more precisely. [4][5][6][13][14][15][16][17][18][19][20] For example, a retrospective, population-based study from Spain found that among children ,24 months old hospitalized with laboratory-identified RSV, 9% were ,1 month of age, similar to our findings; however, their rate of RSV hospitalizations among infants ,1 month of age was more than twice ours (31 per 1000 vs 13.5 per 1000, respectively). 19 Another study estimated a notably high annual rate of RSV-associated hospitalizations among infants #3 months old, 48.9 per 1000 children, which is more than twice the rate we found.…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…Although recent studies, most of which were retrospective assessments, have consistently shown RSV hospitalizations to be the highest in the first year of life, very few have dissected the exact age of RSV-specific hospitalizations more precisely. [4][5][6][13][14][15][16][17][18][19][20] For example, a retrospective, population-based study from Spain found that among children ,24 months old hospitalized with laboratory-identified RSV, 9% were ,1 month of age, similar to our findings; however, their rate of RSV hospitalizations among infants ,1 month of age was more than twice ours (31 per 1000 vs 13.5 per 1000, respectively). 19 Another study estimated a notably high annual rate of RSV-associated hospitalizations among infants #3 months old, 48.9 per 1000 children, which is more than twice the rate we found.…”
Section: Discussionsupporting
confidence: 86%
“…27 However, the effect varied according to age and multiple factors associated with crowding. 14,17,29 In our study, the proportion of hospitalized children residing in homes with other children ,5 years old was more than twice that of children living with older children.…”
Section: Discussionmentioning
confidence: 43%
See 3 more Smart Citations